Prediksi Harga Cabe Rawit di Wilayah Provinsi Sumatera Utara dengan Metode Simple Exponential Smoothing - Gracetira, Naomi; Simamora, Vony Melinda; Margareta, Nokia; Anata P., Josua Pedro; Lingga, Joy Syahputra; Ginting, Kevin Ginsigel; Sarkis S., Indra M. (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
This study aims to predict the price of cayenne pepper in North Sumatra Province using the Simple Exponential Smoothing (SES) method with α = 0.2. The data used includes the price trend of cayenne pepper from January to July 2024, taken from Databoks and supported by BAPANAS (Badan Pangan Nasional). The analysis results show that the SES method can capture the upward trend in the price of cayenne pepper with a relatively high level of accuracy, indicated by the MAPE (Mean Absolute Percentage Error) value of 7.34%. The predicted average price of cayenne pepper on July 15, 2024 is estimated to reach Rp. 47,555.34. These findings suggest that the SES method is reliable for planning and decision-making regarding the price of cayenne pepper, although it is more sensitive to recent data. This research makes an important contribution to the government, farmers, and traders in dealing with fluctuations in agricultural commodity prices.